The effect of educational intervention based on the theory of planned behaviour on promotion of traffic-safe behaviours in students - Mehdi Amirkhani; Fatemeh Balaghi Inalu; Ali Arman; Mahshid Zarghamian; Pooyan Afzali Harsini; Ali Khani Jeihooni (International Journal of Adolescence and Youth)
A quasi-experimental study was conducted in 2023–2024 on 200 fourth- and fifth-grade primary school kids in Fasa City, Iran. Data on demographics, theory of planned behaviour (TPB) components, and traffic patterns were collected. Both the experimental and control groups filled out the questionnaire before and 3 months following the intervention. The experimental group received eight 45–50-minute sessions, which included small group discussions, Q&A sessions, hands-on demonstrations, videos, PowerPoint presentations, and booklets. Before the intervention, there were no significant differences between the groups in knowledge, attitude, subjective norms, perceived behavioural control, behavioural intention, or traffic-safe behaviour, according to the results. Three months following the intervention, the experimental group demonstrated significant improvements in all TPB constructs. This study contributes novel findings by demonstrating the sustained impact of TPB-based education on children’s traffic safety in Iran, offering a practical and effective model for future programmes.